2006
DOI: 10.2495/sdp-v1-n1-76-90
|View full text |Cite
|
Sign up to set email alerts
|

A case study on stabilization and reuse of geopolymer-encapsulated brown coal fly ash

Abstract: Fly ash disposal for coal power stations is an ongoing problem. This paper explores the use of a geopolymeric material to stabilize fly ash and reduce the leach rates of metals, and at the same time determine whether the stabilized material can be reused and recycled as value-added products. Fly ash from the Latrobe Valley, Victoria, Australia, was collected and stabilized in a geopolymer with a molar silica to alumina ratio of 3. Fly ash was collected from electrostatic precipitators [precipitator fly ash (PF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, due to its high organic and oxygen content, lignite is desired for development as a feedstock for value-added chemicals and products [114,115]. Such value-added products may include geopolymers from coal 'gangue' (defined as the solid waste discharged during coal mining and coal washing) and/or activated lignite [116][117][118], iron-containing humics-stabilized nanoparticles [114], and carbonic nanostructures [119,120]. Early work by Haider and Martin [124] showed that cultures of the ascomycete Epicocium nigrum produced HA in vitro, which was evidenced by the formation of polymers and disappearance of substrate phenols.…”
Section: Humic Substance Productionmentioning
confidence: 99%
“…However, due to its high organic and oxygen content, lignite is desired for development as a feedstock for value-added chemicals and products [114,115]. Such value-added products may include geopolymers from coal 'gangue' (defined as the solid waste discharged during coal mining and coal washing) and/or activated lignite [116][117][118], iron-containing humics-stabilized nanoparticles [114], and carbonic nanostructures [119,120]. Early work by Haider and Martin [124] showed that cultures of the ascomycete Epicocium nigrum produced HA in vitro, which was evidenced by the formation of polymers and disappearance of substrate phenols.…”
Section: Humic Substance Productionmentioning
confidence: 99%
“…Geopolymer is emerged as possible technological solution for the effective management of solid industrial wastes, as it achieves to turn a numerous of them into added value products [2,3,4,5], and stabilize and/or immobilize hazardous and toxic materials [6,7,8,9,10,11]. Geopolymers are further more touted for their high performance (high strength and durability), low CO 2 emission and low energy consumption.…”
Section: Introductionmentioning
confidence: 99%